Non-linear relationship between food resource exploitation and population density of stored-product pests - V. Stejskal (Czech Journal of Food Sciences, 2000)
The main current strategies (IPM, HACCP) to control pests in stored food products are based on critical thresholds derived from pest population density. These thresholds usually do not consider cumulative effects of earlier pest infestation although injuries caused by biotic pest organisms to stored food commodities are irreversible. We present conceptual and illustrative models showing that population size indices, in contrast to cumulative (population history) indices, could (i) underestimate critical thresholds if pest population can grow exponentially and (ii) provide incorrect information about the level of stored food damage if pest population density can fluctuate. The importance of entomological food microanalysis and continual "cumulative monitoring" based on trapping is discussed with respect to HACCP and IPM programmes in stored food products.